Penggunaan dinar emas dan dirham perak sebagai mekanisme dalam sistem kewangan - Samat, Abdul Basit; Salamon, Hussin; Ismail, Zuhaimy; Suratman, Azmi Shah; Hassan, Ahmad Muhyuddin; Abdullah, Abdul Hafiz (UTM, 2005)
The decrease of currency value often occurs. Our own country with no exception encounters this situation as it is in the case that in 1997-1998. The situation urges us to carry out a research on the position of currency nowadays. In fact, the phenomenon of currency imbalance is not surprising. This is because, money which has been used now is only a piece of paper imprinted with a certain value. In other words, money used is not based on anything that we can ensure its. The basis of currency is merely lies on the value created by the world economic power. As a comparison, a long time ago, we could talk about the value of a single cent but today it has been devalued. In fact, the power of purchase is declining from time to time. In facture, what was happened to the value of the one cent might also happen to the value of ringgit. Why does is happen? What is the alternative to be taken to ensure the power of currency? Any currency which has no basis is not considered real money. The revival of Gold Dinar and Dirham is not something new. As a matter of fact it had been used long before the printed money was introduced. Gold Dinar and Dirham as an exchange medium give a solid position to the money and they will also prohibit it from any kind of speculation, manipulation and so on. Currency market has turned into afield whereby certain people play the market. Thus, the currency that does not have any guarantee of stability will subject to manipulation for it owns no intrinsic value. The wide practice of riba by the using of printed money is considered as a weapon employed by the enemies of Islam to dominate the Muslim's economy. Besides that, this paper will on evolution of currency, the issues of the genuine money as well as the position of today's money. The researcher will also focus on how to revive the implementation of Gold Dinar and Dirham in the current economic practice through the establishment of an appropriate mechanism